2013
DOI: 10.1097/inf.0b013e31826fd4af
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcus Meningitis in Children

Abstract: GAS meningitis is associated with high mortality and with a high diversity of GAS emm-types and virulence determinants in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 60 publications
0
18
1
2
Order By: Relevance
“…A literature review since 1966 reveals 17 documented cases of neonatal meningitis with CSF cultures positive for group a streptococcus [1,2,4,[6][7][8][9][10][11][12][13][14][15] (Table 1). The previously published reports originated in the following countries: Brazil (N = 4), USA (N = 3), the UK (N = 3), Morocco (N = 2), India (N = 1), Israel (N = 1), Saudi Arabia (N = 1), The Netherlands (N = 1) and Turkey (N = 1).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A literature review since 1966 reveals 17 documented cases of neonatal meningitis with CSF cultures positive for group a streptococcus [1,2,4,[6][7][8][9][10][11][12][13][14][15] (Table 1). The previously published reports originated in the following countries: Brazil (N = 4), USA (N = 3), the UK (N = 3), Morocco (N = 2), India (N = 1), Israel (N = 1), Saudi Arabia (N = 1), The Netherlands (N = 1) and Turkey (N = 1).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the early half of the twentieth century, Streptococcus pyogenes (group a streptococcus (GAS)) was considered a prevalent and important cause of neonatal sepsis and meningitis. However, since the advent and widespread use of antibiotics, it has become a rarely reported cause of neonatal sepsis [1][2][3], often accompanied by a rather severe and occasionally fatal disease course [1,2,[4][5][6]. Here, we review the clinical characteristics of previously reported cases of and present a case of GAS meningitis in a 10-day old, well appearing neonate, most likely resulting from maternal transmission.…”
Section: Introductionmentioning
confidence: 95%
“…Previous reports have demonstrated that GAS meningitis accounts for <2% of cases of pyogenic meningitis in the United States (5) and Netherlands (6), and surprisingly no cases in Canada (7). However, the case fatality rate is reported to be high: 43% in children (8) and 27% in adults (6). Even among survivors, neurological sequelae are observed in 43% of adult patients (6).…”
Section: Introductionmentioning
confidence: 96%
“…La enfermedad invasiva del estreptococo del grupo A (GAS) es una causa aumento de morbilidad y mortalidad, y su incidencia ha ido en aumento en países industrializados. La meningitis por este germen es una enfermedad especialmente rara (9)(10)(11) .…”
Section: Introductionunclassified